Pengaruh Beban Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan biMBA AIUEO Unit Pasif Jakarta Barat - Lestari, Astri; Suryani, Desy (CV Warnak Johanna Nusantara, 2025)
The study aims to examine the impact of workload (X1) and compensation (X2) on job satisfaction (Y) of employees at biMBA AIUEO Pasif Unit, West Jakarta. This study employs a quantitative method, with data collected through the distribution of questionnaires. The study population consists of 113 individuals, with 88 respondents selected as the sample. The analysis involves a series of tests including validity and reliability testing, classical assumption checks, multiple linear regression, hypothesis testing, and the calculation of the determination of IBM SPSS Statistics version 27. The partial hypothesis test results show that workload (X1) has a positive and significant impact on employee job satisfaction, with a t-value of 3.833 exceeding the significance threshold of 0.000 < 0.05 and the t-table value of 1.988. With a t-value of 6.278, higher than the t-table value of 1.988 at a significance threshold of 0.000 < 0.05, the salary variable likewise significantly and favorably affects work satisfaction. The simultaneous hypothesis test indicates that both workload and compensation have a significant impact on job satisfaction, with an F-value of 76.210, greater than the F-table value of 3.10, and a significance level of 0.000 < 0.05.